أثر العدالة التنظيمية في العلاقة بين استراتيجية التدريب والتمكين الإداري وتحسين الأداء الوظيفي للعاملين في دائرة الموارد البشرية ﺑﺈمارة الشارقة بدولة الإمارات العربية المتحدة - عبد لله سليمان عبد لله الكابوري النقبي
the training strategy and organizational empowerment and improving the job performance of employees in the Human Resources Management Department in the Emirate of Sharjah in the United Arab Emirates. The study is important in examining organizational justice and its impact on the relationship between the training strategy and organizational empowerment with the job performance of employees in the Human Resources Department in the Emirate of Sharjah.The study followed the quantitative approach, and accordingly a questionnaire was designed to collect data for analysis. ٤۰۰ questionnaires were distributed to the employees of the Human Resources Department, and ۳٥۱ were answered, which were valid for analysis.The Statistical Package for Social Sciences program (SPSS) was used to analyse the descriptive data and the structural equation modelling program was used (Smart-PLS) which tested for complex variables simultaneously, taking into account the mediating variable. The results of the study indicated that the training strategy and organizational empowerment has a positive and direct impact on improving job performance. This result indicates that there is a clear discrepancy in the role provided by the Human Resources Management Department in the Emirate of Sharjah in improving the job performance of employees in the Emirate of Sharjah. With regard to the mediating variable, the study found that organizational justice plays a partial mediating role in the relationship between the training strategy and organizational empowerment in improving job performance. The study recommended the need to expand the application of the strategic training in all departments in the Emirate of Sharjah and generalize it to all governmental and private institutions in the United Arab Emirates.